P4_9 Tether Propulsion to Geosynchronous Transfer Orbit - Hague, Peter; Tilley, Fred; Davis, Claire (Physics Special Topics, 2011)
A tether system is proposed as a means of lifting payloads from low Earth orbit (LEO) to geosynchronous transfer orbit (GTO).Â The electromagnetic interaction of such tethers with the Earth’s magnetic field and plasma has been tested on orbit and is not discussed. The stresses on such a tether are found to be manageable and the mass less than that of the ISS. Although possibly challenging, this technique would produce significant savings on the mass needed to be placed on orbit.